1987
DOI: 10.1016/0021-9681(87)90176-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cost sharing on the use of antibiotics in ambulatory care: Results from a population-based randomized controlled trial

Abstract: Little is known about how generosity of insurance and population characteristics affect quantity or appropriateness of antibiotic use. Using insurance claims for antibiotics from 5765 non-elderly people who lived in six sites in the United States and were randomly assigned to insurance plans varying by level of cost-sharing, we describe how antibiotic use varies by insurance plan, diagnosis and health status, geographic area, and demographic characteristics. People with free medical care used 85% more antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 15 publications
3
16
0
2
Order By: Relevance
“…That is, higher levels of prescription drug cost sharing actually decrease inappropriate drug use with a relatively inelastic price elasticity of demand of −0.024 (p = 0.004). This result is in line with other studies in the literature which have found that higher cost sharing leads patients to decrease the use of both effective and ineffective medications [18,19]. There are few estimates of the price elasticity of demand for prescription drugs among the elderly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That is, higher levels of prescription drug cost sharing actually decrease inappropriate drug use with a relatively inelastic price elasticity of demand of −0.024 (p = 0.004). This result is in line with other studies in the literature which have found that higher cost sharing leads patients to decrease the use of both effective and ineffective medications [18,19]. There are few estimates of the price elasticity of demand for prescription drugs among the elderly.…”
Section: Discussionsupporting
confidence: 92%
“…Data from the RAND experiment [18], which looked at non-elderly participants across six sites in the US, indicated that individuals with higher coinsurance rates decreased their use of both effective and ineffective antibiotics. Using aggregate data from New Hampshire, Soumerai et al [19] determined that a limit on the number of reimbursable prescriptions, which is essentially 100% coinsurance, reduced the number of essential and discretionary medications obtained among low-income Medicaid recipients.…”
Section: Related Literature and Backgroundmentioning
confidence: 97%
“…According to the WHO,1 50% of medicines are prescribed, dispensed or sold inappropriately, whereas 50% of patients take their medicines incorrectly 2. Inappropriate antibiotic use can lead to antibiotic resistance, resulting in difficult or impossible to treat infections 3.…”
Section: Introductionmentioning
confidence: 99%
“…7 Cost sharing reduced overall spending on antibiotics, but appropriate and inappropriate uses were reduced at the same rate. 8 Improved quality may reduce costs. Better management of chronic conditions in outpatient settings can prevent hospitalizations.…”
Section: It's How You Spend Not How Much You Spendmentioning
confidence: 99%